1993
DOI: 10.1096/fasebj.7.13.7691671
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nitric oxide synthase by syncytiotrophoblast in human placental villi

Abstract: The endogenous biosynthesis of nitric oxide (NO) is increased during gestation. To begin our investigation of a possible tissue source (or sources), we examined the placenta. We postulated that analogous to the endothelium of blood vessels, the syncytiotrophoblast (STr) cell layer that lines the intervillous blood space of the human placenta would express NO synthase. Our results show that human placental villi express a calcium- and calmodulin-sensitive form of NO synthase, located mainly in the microsomal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
90
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 0 publications
12
90
1
1
Order By: Relevance
“…In addition, the data show that NO production reached a peak at day 15.5 of gestation and declined during the last few days of gestation, as NO production in the 15.5-day placenta was 2.6-fold greater than that of the term placenta. Although several studies have demonstrated the presence of NOS in the placenta [5,13,14,23], to the best of our knowledge, the present study is the first report that shows the developmental time-course of NO production in the rat placenta during pregnancy.…”
mentioning
confidence: 57%
“…In addition, the data show that NO production reached a peak at day 15.5 of gestation and declined during the last few days of gestation, as NO production in the 15.5-day placenta was 2.6-fold greater than that of the term placenta. Although several studies have demonstrated the presence of NOS in the placenta [5,13,14,23], to the best of our knowledge, the present study is the first report that shows the developmental time-course of NO production in the rat placenta during pregnancy.…”
mentioning
confidence: 57%
“…Indeed, it was recently shown that the eNOS promoter contains a hypoxia response element and thus might be a HIF target gene (11). Expression of iNOS and eNOS has been observed in human and murine placenta (10,41,45). Thus hypoxic upregulation of placental NOS expression may result in NO-mediated vasodilation, thereby increasing placental blood flow and reconstituting oxygen supply to the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…The placenta is capable of generating NOs, 17 which can in turn react with superoxide to form peroxynitrite anions (ONOO Ϫ ) that covalently modify proteins by nitration of tyrosine residues. 18 Accordingly, we also used immunolocalization techniques to determine whether the apparent preeclampsia-associated changes in invasive cytotrophoblast XDH/XO staining and XO activity were accompanied by changes in the oxidative status of the tissue.…”
Section: The Effects Of Preeclampsia On Nitrotyrosine Generation By Cmentioning
confidence: 99%